Modeling of a photovoltaic system connected to the grid considering the variation of solar irradiance in Homer Pro (2022)
In this research, the need arose to use didactic tools that allow to know the best optimization of a photovoltaic system to supply the loads of the banana company. According to the following statement, this study presents a model and simulation of a grid-connected system, considering the variation of solar irradiance. First, the pyranometer instrument was used in the area to be studied. Then, the loads of the banana plantation were considered, and then the HOMER Pro tool was used to find the best feasibility of the photovoltaic system with its optimization algorithms. For its validation, other algorithms of mathematical models made in Matlab/Simulink were used, establishing the power of the system, the levelized cost of energy (S/kWh), as well as the voltage (V), current (A) and power (W) of both the solar panel and the energy that goes to the load, moreover, the maximum power transfer point (MPPT) of the system was also determined. Finally, the payback of the modeling was evaluated to know the payback time of the system investment.